AUDIT OPERASIONAL UNTUK MENILAI EFEKTIVITAS PENGELOLAAN PERSEDIAAN OBAT PADA RUMAH SAKIT SAIFUL ANWAR MALANG - Wulan Pratiwi Purbosari (Jurnal Ilmiah Mahasiswa FEB, 2019)
The research on operational auditing in the medicine supply management of Saiful Anwar Hospital Malang aims to assess the effectiveness of, determine the obstacle in, and provide recommendation for the medicine supply management. This qualitative descriptive research utilizes secondary data and primary data collected through observation, interview, and documentation. The scope of the research is the medicine supply management including pharmacy supply selection, planning, procurement, receipt, storage, distribution, annihilation & withdrawal, controlling and administration. The research indicates that the medicine supply management of Saiful Anwar Hospital Malang has been working effectively as regulated, despite some implementation obstacles. This research, therefore, also provides recommendation to consider for more effective operational activity.Keywords : Operational Auditing, Effectiveness, Supply Function.